Towards a trustworthy RFID system - from a security perspective. (22nd February 2021) - Zuo, Yanjun
This paper presents a comprehensive, layered framework for a trustworthy radio frequency identification (RFID) system, which has been applied in various fields such as supply chain management, inventory tracking, healthcare, transportation and logistics, manufacturing, library, agriculture, payment and asset management. RFID provides real-time data and analytics, which allow organisations to have more accurate information at all time for improved decision making. Our proposed framework addresses technical challenges of building trustworthy RFID systems given the resource-constricted RFID components as well as high mobility and sensitivity of RFID devices. The framework offers the following merits: 1) it can be used in vastly distributed environment to support large scope RFID-enabled business processes; 2) it is appropriate for resource-restricted RFID system components; 3) it provides users with the most trustworthy information about RFID tagged items despite malicious attacks; 4) it can tolerate attacks at RFID system level and higher-application level.